The Impact Of Corruption On Economic Development: Case Study Romania - Ionescu, Luminita; Caloian, Florentin (Annals of Spiru Haret University. Economic Series, 2016)
In the last decade, Romania implemented a strong legislation and a comprehensive program of public financial management reform in order to improve the national fiscal transparency and to reduce corruption. Corruption is a growing phenomenon all over the world, affecting economic development and aggravated by the legacy of the global economic crisis. The global risks are different from the past due to notably cyber attacks, new economic realities and geopolitical risks. Most of the time, corruption is associated with financial crime, fraud and bribery. Corruption is a major factor of reducing economic development and the governments must increase of macroeconomic and fiscal forecasts in order to facilitate access to the public funds.